Numerical evaluation of slope effect on soil–pile interaction in seismic analysis. (September 2022) - Tran, Nghiem Xuan; Gu, Kyo-Young; Yoo, Mintaek; Kim, Sung-Ryul
Highlights: Failure modes of piles under lateral loading significantly affected by slope angle. Transition depth of failure modes ranging from two-pile diameter to ten-pile diameter. Proposed formulation for effects of slope and confining stress on soil–pile interface. A developed model accounting for the soil–pile separation. Numerical validation of proposed lateral soil–pile interface in seismic analysis. Abstract: This study aims to evaluate the slope effect on the behavior of soil–pile interface in the lateral direction, which is a factor governing the seismic response of pile-supported structures. A series of numerical simulations of a single pile in cohesionless soil subjected to lateral loading were performed by considering various slope configurations, soil densities, and loading directions. The lateral and confining forces acting at the soil–pile interface increased at a comparable rate under increasingly lateral loading. The ratio of the ultimate lateral force to the ultimate confining force was defined as a lateral interface-force ratio, which was introduced to quantify the slope effect on the strength parameter of the lateral soil–pile interface. The lateral interface–force ratio increased together with embedment depth and maintained a constant value below a certain depth corresponding to the change in failure mechanism from the wedge mode to the flow mode. In addition, an interface model of the soil–pile separation due to the slope failure was developed for the numerical analysis of piles in the cohesionless soil. Finally, the proposed lateral soil–pile interface was implemented via a three-dimensional numerical simulation of a dynamic centrifuge test for the validation work. The good agreement between the numerical simulation and experimental data indicates the reasonable applicability of the proposed interface properties.